Eksplorasi Implementasi Green Accounting pada Sektor Pemerintahan: Sebuah Tinjauan Bibliometrik: Exploring Green Accounting Implementation in Government: A Bibliometric Review - Indra Basir; Nur Fitriani; Muhammad Ihsan Ansari; Hisyam Ichsan (Journal of Economic, Public, and Accounting (JEPA), 2026)
Environmental degradation and climate change have encouraged governments to adopt sustainable development policies, including the implementation of green accounting. Although studies on green accounting in the public sector have grown considerably, bibliometric analyses that comprehensively map this research area remain limited. This study aims to analyze publication trends, the contributions of journals, institutions, and countries, as well as to identify the most influential authors, articles, and research topics related to the implementation of green accounting in the government sector. A bibliometric analysis was conducted on 364 documents indexed in the Scopus database from 1994 to 2024 through data collection, screening, visualization, and interpretation. The findings indicate that publications on green accounting in the government sector have increased significantly over the past two decades. Accounting, Auditing & Accountability Journal is the most productive journal in this field, while the United Kingdom has the highest publication contribution and the strongest international collaboration with Australia. The most frequently occurring keywords are accountability, government, and sustainability. These findings provide valuable insights for policymakers and researchers in strengthening public accountability and promoting sustainable development.